“It is something that gives us hope”: Lived experience among parents to children with cerebral palsy who are non-ambulant of the phenomenon physical activity, with or without the use of a novel dynamic standing device - Lauruschkus, Katarina; Holmberg, Robert; Tornberg, Åsa B. (Frontiers in Rehabilitation Sciences, 2023)
Introduction: Regular physical activity confers health benefits for all. Parents commonly want their children to be physically active, and want to be physically active themselves, but children with cerebral palsy (CP) who are non-ambulant face challenges, and they need support to be physically active. Dynamic standing in the novel motorized assistive device Innowalk has positive effects for children who are non-ambulant – it gives them a chance to be physically active. The aim of this study was to explore the lived experience of physical activity of parents themselves and for their children with cerebral palsy who are non-ambulant. Methods: A descriptive inductive design with a hermeneutic phenomenological approach was used for the analysis of interviews with 11 parents of children with CP who are non-ambulant who participated in a study of exercise effects of dynamic standing. Results: The parents experienced physical activity for their children as being important but difficult, especially for their child, as described in Theme 1: “Being aware of health benefits while struggling with family time”. The children were perceived as being dependent on other people, the environment, and equipment for participating in physical activity, referring to Theme 2: “Being dependent”. The opportunity for their children to become physically active on a regular basis through an assistive device gave the parents hope for a better life, which formed Theme 3: “Getting hope in a challenging life situation”. Conclusion: Physical activity for children with CP who are non-ambulant is possible through an elaborate network of social relations and environmental conditions. Limiting the degree of dependence and containing the negative consequences of high a degree of dependence are vital in the support of physical activity. Relations, support, and assistive devices that strengthen empowerment and autonomy should be prioritized, and if this works, the experience of physical activity can be positive, giving families hope.